Sorafenib versus Lenvatinib Causes Stronger Oxidative Damage to Membrane Lipids in Noncancerous Tissues of the Thyroid, Liver, and Kidney: Effective Protection by Melatonin and Indole-3-Propionic Acid - Jan Stępniak; Joanna Krawczyk-Lipiec; Andrzej Lewiński; Małgorzata Karbownik-Lewińska (Biomedicines, 2022)
Sorafenib and lenvatinib are multi-targeted tyrosine kinase inhibitors which are currently approved to treat advanced hepatocellular carcinoma, renal cell carcinoma and radioiodine-refractory differentiated thyroid carcinoma. However this treatment is often limited due to common adverse events which may occur via oxidative stress. The study aims to compare sorafenib- and lenvatinib-induced oxidative damage to membrane lipids (lipid peroxidation, LPO) in homogenates of porcine noncancerous tissues of the thyroid, the liver, and the kidney and to check if it can be prevented by antioxidants melatonin and indole-3-propionic acid (IPA). Homogenates of individual tissues were incubated in the presence of sorafenib or lenvatinib (1 mM, 100 µM, 10 µM, 1 µM, 100 nM, 10 nM, 1 nM, 100 pM) together with/without melatonin (5.0 mM) or IPA (5.0 mM). The concentration of malondialdehyde + 4-hydroxyalkenals, as the LPO index, was measured spectrophotometrically. The incubation of tissue homogenates with sorafenib resulted in a concentration-dependent increase in LPO (statistically significant for concentrations of 1mM and 100 µM in the thyroid and the liver, and of 1 mM, 100 µM, and 10 µM in the kidney). The incubation of thyroid homogenates with lenvatinib did not change LPO level. In case of the liver and the kidney, lenvatinib increased LPO but only in its highest concentration of 1 mM. Melatonin and IPA reduced completely (to the level of control) sorafenib- and lenvatinib-induced LPO in all examined tissues regardless of the drug concentration. In conclusion, sorafenib comparing to lenvatinib is a stronger damaging agent of membrane lipids in noncancerous tissues of the thyroid, the liver, and the kidney. The antioxidants melatonin and IPA can be considered to be used in co-treatment with sorafenib and lenvatinib to prevent their undesirable toxicity occurring via oxidative stress.